THE TREND OF NOTIFIED OCCUPATIONAL DISEASES AND POISONING IN PAHANG: ACHIEVEMENT AND FUTURE CHALLENGES - GOVINDASAMY, KESAVAN; SAMSUDDIN, NIZA (International Journal of Allied Health Sciences, 2022)
Introduction: The notification requirements on occupational diseases and poisoning are stated clearly in the Occupational Safety and Health (Notification of Accident, Dangerous Occurrence, Occupational Poisoning and Occupational Disease) Regulation 2004 [NADOPOD] (OSHA, 1994). Nevertheless, the number of notifications remain low compared to the number reported in developed countries. In view of occupational disease and poisoning under-reporting issues, the Department of Occupational Safety and Health (DOSH), Pahang has implemented few intervention programmes for notification improvement in line with the Occupational Safety and Health Master Plan (OSHMP 2020) strategies. The intervention programmes include firm punitive actions against non-compliance to the NADOPOD regulations 2004, standard settings and promotional activities. The aim of this study is to discuss the trend of occupational disease and poisoning notification in Pahang post-intervention programmes. Methods: Secondary data on occupational disease and poisoning based on DOSH Pahang’s database from 2016-2019 was collected and descriptively analysed. The total cases of reported occupational disease and poisoning was 1867 cases. Results: There was an increasing trend of the occupational diseases and poisoning notification within the study period. In 2019, DOSH Pahang has successfully responded to OSHMP 2020 targets where there has been an increased in notifications of more than 30 percent as compared to 2016. Firm legislative enforcement, standard settings and promotional activities are the main reasons of the increased in the notifications. Among the notified cases, the highest is occupational noise related hearing disorders (1776, 95.1%). Nevertheless, the notification of other occupational diseases was scanty. It is believed that comprehensive and clear guidelines for both work environment and worker’s surveillance for noise exposure bound by legislative requirements are the major reasons of the highest notifications for occupational noise related hearing disorders. Conclusion: The study suggests for using a similar approach to increase the notification of other occupational diseases and poisoning to improve notification.